An audit of the time spent by patients in the post anesthetic care unit before and after the introduction of a discharge criteria scoring system at Tygerberg Academic Hospital - Dwyer, Sean (Stellenbosch : Stellenbosch University, 2014)
Thesis (MMed)--Stellenbosch University, 2014.